Distribution of Rice Plant Pests (Oryza sativa L.) in Vegetative and Generative Phases: analytical study - Moh Khafid Nasrullah; Akbar Rafsanjani (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Rice as one of the main foods that experience many obstacles in doing cultivation. One of them is insect pest attack. This study aims to study the activity of insect pests that damage rice plants to inhibit their growth and development. Increasing rice production in Indrapuri District, Aceh Besar District continues to be pursued. This research activity was carried out from April to June 2019, by adopting the observation method to detect the presence of types of pests by using sweeping equipment in the form of a net at the location of rice field plots. The collection of pests from the insect group is carried out by identifying them which refers to the insect identification key. The results showed that insect and non-insect types of pests were found that were destructive in both the vetetative and generative phases to inhibit their growth and development which had a negative impact on production.